Phytotherapeutic Interventions Targeting Microvascular Dysfunction in Early Non-Proliferative Diabetic Retinopathy: A Systematic Review and Meta-Analysis of Effects on Retinal Perfusion and Function - Ramzi Amin; Muhammad Baqir (Eureka Herba Indonesia, 2025)
Microvascular dysfunction, encompassing impaired perfusion and subsequent functional deficits, is a hallmark of early non-proliferative diabetic retinopathy (NPDR). Phytotherapeutic agents, with their potential antioxidant, anti-inflammatory, and vasculoprotective properties, have emerged as candidate interventions. However, synthesized evidence regarding their specific impact on retinal perfusion and function in early NPDR remains limited. This systematic review and meta-analysis aimed to evaluate the efficacy of phytotherapeutic interventions on quantitative measures of retinal perfusion and visual function in patients with early NPDR. A systematic literature search was conducted in PubMed, Embase, Scopus, and the Cochrane Central Register of Controlled Trials (CENTRAL) for randomized controlled trials (RCTs) published between January 2013 and December 2024. Studies evaluating any phytotherapeutic intervention versus placebo or standard care in patients with early NPDR, reporting outcomes related to retinal perfusion (including Foveal Avascular Zone [FAZ] area, capillary density via Optical Coherence Tomography Angiography [OCT-A]) or retinal function (including Best-Corrected Visual Acuity [BCVA], Contrast Sensitivity [CS], electroretinogram [ERG] parameters) were considered. Data from seven RCTs meeting eligibility criteria were analyzed. Data extraction and risk of bias assessment (Cochrane RoB 2 tool) were performed. Meta-analyses using a random-effects model were conducted for key outcomes, calculating Mean Differences (MD) or Standardized Mean Differences (SMD) with 95% Confidence Intervals (CIs). Heterogeneity was assessed using the I² statistic. Seven RCTs (total N=585 patients) were included. The interventions evaluated included Ginkgo biloba, Bilberry extract, Curcumin, Saffron, Pycnogenol, Mirtogenol, and a standardized Traditional Chinese Medicine (TCM) formula. Risk of bias across the studies varied, with concerns primarily in blinding and outcome measurement domains in some trials. Meta-analysis indicated that phytotherapeutic interventions were associated with a statistically significant improvement in retinal perfusion markers compared to control. This included a reduction in FAZ area (MD: -0.04 mm², 95% CI [-0.06, -0.02], P<0.001; I²=58%) and an increase in parafoveal superficial capillary density (MD: +1.85 %, 95% CI [+1.10, +2.60], P<0.001; I²=65%). Functional improvements were also observed, including BCVA (MD: -0.03 logMAR, 95% CI [-0.05, -0.01], P=0.005; I²=35%) and contrast sensitivity (SMD: 0.35, 95% CI [0.15, 0.55], P<0.001; I²=48%). Safety data suggested no significant increase in major adverse events compared to control groups (Risk Ratio: 1.12, 95% CI [0.75, 1.68], P=0.58; I²=0%). In conclusion, this systematic review and meta-analysis found that phytotherapeutic interventions improve retinal microvascular perfusion and associated visual function in patients with early NPDR, with an acceptable safety profile. These findings support the potential role of specific phytotherapies as adjunctive treatments in managing early diabetic microvascular changes. Further large-scale trials are warranted to confirm these benefits and explore long-term outcomes.